Preparation method of zinc-based coordination compound and application of zinc-based coordination compound in gas separation

By using the SQL topology adsorption agent using Zn-MOF materials, the problem of high energy consumption and environmental impact on the existing gas separation process, and realizing the separation of carbon dioxide in low energy, high-efficiency acetylene and methane carbon dioxide, showing that it was in Gas separation potential.

CN119371675AActive Publication Date: 2025-01-28CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411495547.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing gas separation process has high energy consumption and adversely affects the environment, making it difficult to efficiently separate high-purity acetylene and carbon dioxide impurities in methane.

Method used

The Zn-MOF material is used, and its chemical formula is [Zn2 (H2O) 4 (TCPB-ME)], which forms adsorption materials with SQL topology at room temperature through simple preparation methods.

Benefits of technology

Achieving low energy and high -efficiency gas separation, especially in the field of separation of C2H2/CO2 and CO2/CH4, shows the potential of good thermal stability and porous materials for composite function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371675A_ABST
    Figure CN119371675A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new materials, and particularly relates to a Zn-MOF material and a preparation method and application thereof. The chemical general formula is [Zn2 (H2O) 4 (TCPB-Me)], Zn is a divalent zinc ion, and TCPB-Me is a deprotonated 1, 2, 4, 5-tetra (4-carboxyphenyl)-3, 6-xylene ligand. The structure of the Zn-MOF material belongs to a P21 / c space group of a monoclinic system, and the cell parameters of the Zn-MOF material are that the axial length is # imgabs 0 #, the axial angle alpha is equal to gamma and is 90 degrees, the beta is equal to 90.989 (10) degrees, and the cell volume is # imgabs 1 # Z and is equal to 4. The preparation method of the Zn-MOF material comprises the following steps: dissolving metal zinc salt and H4TCPB-Me in a mixed solution of an organic solvent and water; sealing and placing in a drying oven at 80-120 DEG C for 24-72 hours; and naturally cooling to room temperature to obtain the Zn-MOF material. Due to the unique structure of the Zn-MOF material, the Zn-MOF material can be applied to the fields of separation of mixed gas C2H2 / CO2 and CO2 / CH4 and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and specifically relates to a preparation method of a zinc-based coordination compound and gas separation application. Background Art

[0002] Acetylene (C2H2) is a key industrial raw material, widely used in the manufacture of basic chemicals such as ethylene, polyvinyl chloride, propylene, butadiene, as well as synthetic materials such as rubber, fiber and plastic. In industry, acetylene is mainly produced by methane oxidation. However, the acetylene produced by this reaction contains a large amount of carbon dioxide (CO2) impurity gas, which affects its efficiency in downstream chemical processes and the quality of the final product. Therefore, efficient separation of high-purity acetylene is of great significance for improving energy efficiency and reducing production costs. In the face of energy shortages and environmental crises, cleaner and more economical gas resources such as natural gas, biogas, shale gas, and coalbed methane have attracted much attention as ideal substitutes for oil and coal. The active ingredient of these gas resources is methane (CH4), which is often mixed with carbon dioxide gas, which will reduce the calorific value of combustion and corrode gas pipelines, and also limit the scope of utilization. Therefore, it is critical to selectively capture CO2 and achieve efficient separation of CO2 / CH4.

[0003] The current gas separation processes mainly include chemical absorption, cryogenic distillation and solvent extraction, which are often energy-intensive and have adverse effects on the environment. For example, cryogenic distillation is based on the difference in liquefaction temperature of each component in the mixed gas to achieve separation, and requires a lot of energy to cool and liquefy the gas; while chemical absorption requires the use of a large amount of solvent and the solvent recovery and regeneration process consumes a lot of energy, and may also produce harmful waste liquids that have a certain impact on the environment. Therefore, there is an urgent need for a low-energy, environmentally friendly separation and purification process and material.

[0004] Compared with traditional separation technology, adsorption separation can be carried out at room temperature and pressure, with relatively low cost and energy consumption. However, traditional adsorbents, such as zeolite, molecular sieve, and activated carbon, have small surface area and porosity, and their structure cannot be adjusted, making it difficult to achieve gas separation. Metal-Organic Framework (MOF) is a crystalline material with a periodic network structure formed by metal ions and organic ligands through a self-assembly process. MOF has strong applicability in gas adsorption, storage and separation, and selective gas adsorption due to its highly ordered pore structure, large specific surface area, and adjustable and modified pore size. It can be used as a low-energy, high-efficiency, and highly adaptable adsorbent. Summary of the invention

[0005] In order to solve the technical problems in the above-mentioned background technology, the present invention provides a Zn-MOF material.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: a Zn-MOF material, the chemical formula is [Zn2(H2O)4(TCPB-Me)], wherein Zn is a divalent zinc ion, and TCPB-Me is a deprotonated 1,2,4,5-tetrakis(4-carboxyphenyl)-3,6-dimethylbenzene ligand. The Zn-MOF material structure belongs to the monoclinic system, the P21 / c space group, and its unit cell parameters are the axial length Axis angle α = γ = 90°, β = 90.989(10)°, unit cell volume is Z=4.

[0007] The beneficial effects of the present invention are:

[0008] 1. The synthesis method of the Zn-MOF material of the present invention has a simple process, mild conditions, and a yield of 45%-50%. After the reaction raw materials are dissolved, the desired material can be obtained by reacting at about 100°C. There are no toxic or harmful substances and catalysts in all the raw materials used, and no toxic or harmful substances are produced during the preparation process.

[0009] 2. Each layer of the Zn-MOF material of the present invention has a triple interlaced structure of sql topology and has excellent thermal stability.

[0010] 3. The Zn-MOF material of the present invention can be used to prepare adsorption materials and proton conduction materials, and is a composite functional porous material with great potential.

[0011] The crystal structure of the Zn-MOF material of the present invention was tested at 150K using Agilent's SuperNova micro-focus X-ray single crystal diffractometer, and data was received on an EosCCD. A graphite monochromator was used, and λ(Cu Kα) was The CrysAlisPro tool was used for data analysis and absorption correction in a variable speed arbitrary angle scanning mode of ω-2θ. All structures were directly solved using the SHELXS program packaged by SHELXTL, and the structure was refined using the SHELXL full matrix least squares method. All non-hydrogen atoms were anisotropically treated, and the hydrogen atoms of the organic ligands were generated by geometric symmetry. The Zn-MOF material structure of the present invention belongs to the monoclinic system, the P21 / c space group, and the basic structural unit of the crystal is obtained by symmetry operation from the asymmetric unit.

[0012] There are 0.5 deprotonated TCPB-Me ligands, 1 zinc ion, and 2 coordinated oxygen atoms in the asymmetric unit.

[0013] The zinc ion is connected to four oxygen atoms in a four-coordinated manner, and these four oxygen atoms come from the oxygen atoms (O5, O6) in the two carboxyl groups (O1-C1-O5, O6-C14-O7) of two different ligands and two water molecules (O2, O4); each Zn atom center combines with two oxygen atoms from two TCPB-Me ligands and two terminal H2O to form a regular tetrahedron. Each TCPB-Me ligand is connected to four Zn atom centers through its four carboxyl oxygen atoms.

[0014] The Zn-MOF material structure belongs to the monoclinic system, P21 / c space group, and its unit cell parameters are the axial length Axis angle α = γ = 90°, β = 90.989(10)°, unit cell volume is Z=4.

[0015] The present invention also provides a method for preparing a Zn-MOF material, comprising the following steps:

[0016] A. dissolving H4TCPB-Me ligand and zinc nitrate hexahydrate in a solvent to obtain a uniform mixed solution, wherein the molar ratio of the H4TCPB-Me ligand to the zinc nitrate hexahydrate is 1:4, and the concentration of the H4TCPB-Me ligand in the solution is 1.7047 mmol / L;

[0017] B. Place the mixed solution described in step A in a glass bottle and keep it warm at 100° C. for 24 to 72 hours to obtain the Zn-MOF material.

[0018] The beneficial effects of the present invention are: the preparation method has simple conditions, the reaction can be carried out quickly, energy is saved, and time is saved. In addition, the preparation method of the Zn-MOF material of the present invention has high yield, small amount of ligand used, and cost saving.

[0019] On the basis of the above technical solution, the present invention can also be improved as follows:

[0020] In the present invention, further, the solvent is N,N-dimethylacetamide and water, and the volume ratio is 1:0.1-10.

[0021] The beneficial effect of adopting the above further scheme is that the solvent composed of N,N-dimethylacetamide and water is easily available, inexpensive, and less polluting, and the prepared Zn-MOF material has a better crystal state.

[0022] In the present invention, further, the molar ratio of the H4TCPB-Me ligand to the zinc nitrate hexahydrate is 1:4, and the concentration of the H4TCPB-Me ligand in the solution is 1.7047 mmol / L;

[0023] The beneficial effect of adopting the above further scheme is that the Zn-MOF material obtained by the determined concentration and molar dosage ratio has a better crystal morphology and the reaction is smoother.

[0024] The present invention also provides an application of a Zn-MOF material in the field of low-carbon hydrocarbon gas separation. The Zn-MOF material performs adsorption tests on single-component CO2, C2H2 and CH4 gases to obtain differentiated adsorption amounts of C2H2 / CO2 and CO2 / CH4 for gas separation.

[0025] The beneficial effect of the present invention is that the Zn-MOF material is applied to the field of C2H2 / CO2 and CO2 / CH4 gas separation, making the function of the Zn-MOF material more comprehensive. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a structural diagram of the asymmetric structural unit of the Zn-MOF material of the present invention;

[0027] Figure 2 The structural diagram of the Zn-MOF material of the present invention: (a) the coordination environment of zinc ions; (b) the formed sql topology; (c) the triple interpenetrating structure and stacking mode; (d) the pores;

[0028] Figure 3 The XRD spectra of the test and simulation of the Zn-MOF material of the present invention, the abscissa is the Bragg diffraction angle, and the ordinate is the diffraction intensity;

[0029] Figure 4 It is a thermal weight loss curve of the Zn-MOF material of the present invention, the abscissa is the temperature, and the ordinate is the weight loss percentage;

[0030] Figure 5 This is the infrared spectrum of the Zn-MOF material of the present invention, where the abscissa is the wave number and the ordinate is the transmittance;

[0031] Figure 6 This is the N2 adsorption isotherm diagram of the Zn-MOF material of the present invention at 77K, where the abscissa is pressure and the ordinate is the adsorption amount;

[0032] Figure 7 is the pore size distribution curve of the Zn-MOF material of the present invention, the abscissa is the pore size, and the ordinate is the pore size distribution;

[0033] Figure 8 It is the adsorption isotherm diagram of CO2, CH4 and C2H2 of Zn-MOF material of the present invention at 273K, the abscissa is the pressure, and the ordinate is the adsorption amount;

[0034] Fig. 9It is the adsorption isotherm diagram of CO2, CH4 and C2H2 of Zn-MOF material of the present invention at 298K, the abscissa is pressure, and the ordinate is adsorption amount;

[0035] Fig.10 The diagram is the adsorption enthalpy diagram of the Zn-MOF material of the present invention for CO2, CH4 and C2H2, where the abscissa is the adsorption amount and the ordinate is the adsorption enthalpy;

[0036] Fig.11 The adsorption selectivity diagram of the Zn-MOF material of the present invention for C2H2 / CO2 and CO2 / CH4 mixed gases at 273K and 298K, respectively, wherein the abscissa is the pressure and the ordinate is the common logarithm of the selectivity; DETAILED DESCRIPTION

[0037] The principles and features of the present invention are described in detail below in conjunction with implementation. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0038] Embodiment 1,

[0039] A method for preparing a Zn-MOF material specifically comprises the following steps:

[0040] A. Accurately weigh 0.0050 g, 0.0085 mmol of 1,2,4,5-tetrakis(4-carboxyphenyl)-3,6-dimethylbenzene (H4TCPB-Me) ligand and 0.0100 g, 0.0336 mmol of zinc nitrate hexahydrate into a reaction container using an analytical balance. At room temperature, add 5 mL of a mixed solvent consisting of N,N-dimethylacetamide and water into the reaction container, wherein the volume ratio of N,N-dimethylacetamide to water is 1:1.

[0041] B. Place the mixed solution in step A in a glass bottle and keep it in a constant temperature blower at 100° C. for 24 to 72 hours to obtain a colorless crystalline Zn-MOF material.

[0042] like Figure 1 and Figure 2 As shown, the colorless crystalline Zn-MOF material was tested at 150K using Agilent's SuperNova micro-focus X-ray single crystal diffractometer, and data was received on an EosCCD. A graphite monochromator was used, and λ(CuKα) was The CrysAlisPro tool was used for data analysis and absorption correction in a variable speed arbitrary angle scanning mode of ω-2θ. All structures were solved directly using the SHELXS program packaged by SHELXTL, and the structure was refined using the SHELXL full matrix least squares method. All non-hydrogen atoms were treated anisotropically, and the hydrogen atoms of the organic ligands were generated by geometric symmetry. The crystal data shown in Table 1, the typical bond length data of the crystal shown in Table 2, and the typical bond angle data of the crystal shown in Table 3 were obtained.

[0043] Table 1: Crystal data

[0044]

[0045]

[0046] Table 2: Typical bond length data of crystals (unit: )

[0047] Zn1 O5 1.954(8) Zn1 O6 1.977(9) Zn1 O3 1.924(6) Zn1 O1 1.940(7) O1 C1 1.243(12) O2 C1 1.232(12) C6 C7 1.384(12) C6 C5 1.391(13) C7 C2 1.372(13) C3 C2 1.388(12) C3 C4 1.388(12) C9 C8 1.385(12) C8 C5 1.480(11) C5 C4 1.364(13) C2 C1 1.508(11)

[0048] Table 3: Typical bond angle data of crystals (unit: °)

[0049]

[0050]

[0051] Combining the crystal data in Table 1, Table 2 and Table 3, the following relevant characterizations of Zn-MOF materials are obtained:

[0052] The asymmetric unit consists of 0.5 deprotonated TCPB-Me ligands, 1 zinc ion, and 2 coordinated oxygen atoms.

[0053] The zinc ion is connected to four oxygen atoms in a tetracoordinate manner, and these four oxygen atoms come from the oxygen atoms (O5, O6) in two carboxyl groups (O1-C1-O5, O6-C14-O7) of two different ligands and two water molecules (O2, O4).

[0054] The carboxyl groups in the ligand (O1-C1-O5, O6-C14-O7) adopt a monodentate bridging mode to connect adjacent Zn atoms, eventually forming a [Zn(H2O)2][COO]2 structure. All carboxyl groups in TCPB-Me are deprotonated and adopt a monodentate bridging mode to connect adjacent Zn atoms, forming a two-dimensional sql topological network. Three two-dimensional sql topological networks are interspersed to form a layer of the framework, and the layers are connected by hydrogen bonds (O2-H2b···O1, bond length ) are connected and stacked to form a three-dimensional frame structure.

[0055] The Zn-MOF material structure of the present invention belongs to the monoclinic system, P21 / c space group, and its unit cell parameters are the axial length Axis angle α = γ = 90°, β = 90.989(10)°, unit cell volume is Z=4.

[0056] like Figure 3 As shown, the colorless crystalline Zn-MOF material is tested by a powder X-ray diffractometer, the Bragg diffraction angle is 3 to 50°, and the diffraction intensity is measured every 0.01°. The Zn-MOF material exhibits a diffraction pattern as shown in the figure. From the diffraction pattern in the figure, it can be seen that the collected Zn-MOF material has good phase purity.

[0057] like Figure 4 As shown, the colorless crystalline Zn-MOF material was subjected to thermogravimetric analysis. The thermogravimetric test was conducted on a Mettler synchronous thermogravimetric analyzer, machine model RGA / DSC-1, the reaction gas and the protective gas were both nitrogen, the flow rate was 25 mL / min, the running time was 50 minutes, the heating rate was 10°C / min, and the test temperature range was 30-900°C. Figure 4 From the thermogravimetric curve, we can see that the Zn-MOF material can be stable to about 492°C; the complex loses the coordinated solvent in the system at 256°C, and the weight loss from 256°C to 492°C is the collapse of the framework. This shows that the Zn-MOF material of the present invention has good stability and can be decomposed at high temperatures.

[0058] like Figure 5 As shown, the colorless crystalline aluminum-based complex was detected by infrared spectroscopy. The infrared test was performed by KBr tablet method and the wavelengths of 4000-400 cm were collected on a Nicolet 330 FTIR spectrometer. -1 Infrared spectrum in the region. Figure 5 It can be seen that the complex is located at 1600cm -1 The absorption peak nearby can be attributed to the stretching vibration peak of the benzene ring skeleton in the ligand, which is located at 1400cm -1 The absorption peaks nearby can be attributed to the symmetric stretching vibration peaks of deprotonated carboxyl groups, which are located at 1300-400 cm -1 The absorption peak in the region is a characteristic peak in the fingerprint region of the Zn-MOF material.

[0059] like Figure 6As shown, the colorless crystalline Zn-MOF material was tested by the ASAP2020 instrument of Mack, USA. The zinc-based complex exhibited an adsorption isotherm for the single component N2 at 77K as shown in the figure. The adsorption isotherm is a type II isotherm with a relatively obvious desorption hysteresis. From the isotherm, it can be obtained that the single-point BET specific surface area of ​​the Zn-MOF material at P / P0=0.2 is 204.765m 2 / g, BET specific surface area is 220.228m 2 / g; the single point value of the total pore volume when P / P0=0.99 is 0.198cm 3 / g, t-plot micropore volume is 0.061cm 3 / g. The pore size distribution is calculated from the N2 adsorption isotherm as follows: Figure 7 shown.

[0060] like Figure 8 and Fig. 9 As shown in the figure, the colorless crystalline Zn-MOF material was tested by the ASAP2020 instrument of the American Micromeritics Company. The zinc-based complex exhibited adsorption isotherms for single-component CO2, C2H2 and CH4 gases as shown in the figure. The adsorption amounts of CO2, C2H2 and CH4 at 273K were 40.5 cm 3 / g, 49.7cm 3 / g and 16.2cm 3 / g, the adsorption capacities of CO2, C2H2 and CH4 at 298K are 29.6 cm 3 / g, 44.1cm 3 / g and 7.9cm 3 / g. Therefore, from the differentiated adsorption amounts in the figure, it can be known that the Zn-MOF material can be applied to the gas separation fields of C2H2 / CO2 and CO2 / CH4.

[0061] like Fig.10 As shown, the adsorption enthalpy of the CO2, C2H2 and CH4 adsorption isotherms is calculated using the Virial formula to obtain the relationship curve between the adsorption enthalpy of CO2, C2H2 and CH4 and the adsorption amount. It can be seen from the figure that the maximum adsorption enthalpy of the Zn-MOF material for CO2, C2H2 and CH4 is 26.64kJ / mol, 46.54kJ / mol, and 30.48kJ / mol, respectively.

[0062] like Fig.11As shown, the adsorption selectivity of the Zn-MOF material to CO2, C2H2 and CH4 is analyzed using the ideal adsorption solution theory, and the selectivity-pressure curve shown in the figure is obtained. It can be seen from the figure that the Zn-MOF material C2H2 / CO2 and CO2 / CH4 both have high adsorption selectivity.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A Zn-MOF material, characterized in that: The general chemical formula is [Zn2(H2O)4(TCPB-Me)], where Zn is a divalent zinc ion and TCPB-Me is a deprotonated 1,2,4,5-tetrakis[4-carboxyphenyl]-3,6-dimethylbenzene ligand. Each Zn atom center combines with two oxygen atoms from two TCPB-Me ligands and two terminal H2O to form a regular tetrahedron. Each TCPB-Me ligand is connected to four Zn atom centers through its four carboxyl oxygen atoms; The Zn-MOF material structure belongs to the monoclinic system, P21 / c space group, and its unit cell parameters are the axial length Axis angle α = γ = 90°, β = 90.989(10)°, unit cell volume is Z=4.

2. A method for preparing the Zn-MOF material according to claim 1, characterized in that: The steps include: A. dissolving H4TCPB-Me ligand and zinc nitrate hexahydrate in a solvent to obtain a uniform mixed solution, wherein the molar ratio of the H4TCPB-Me ligand to the zinc nitrate hexahydrate is 1:4, and the concentration of the H4TCPB-Me ligand in the solution is 1.7047 mmol / L; B. Place the mixed solution described in step A in a glass bottle and keep it warm at 100° C. for 24 to 72 hours to obtain the Zn-MOF material.

3. The method for preparing the zinc-based complex according to claim 2, characterized in that: The solvent consists of N,N-dimethylacetamide and water, and the volume ratio of N,N-dimethylacetamide to water is 1:

1.

4. The method for preparing the Zn-MOF material according to any one of claims 2 or 3, characterized in that: The molar dosage ratio of the H4TCPB-Me ligand to the zinc nitrate hexahydrate is 1:4, and the concentration of the H4TCPB-Me ligand is 1.7047 mmol / L.

5. An application of the Zn-MOF material according to claim 1 in the field of mixed gas separation, characterized in that: The Zn-MOF material was tested for adsorption of single-component CO2, C2H2 and CH4 gases, and the obtained C2H2 / CO2 and CO2 / CH4 adsorption amounts with large differences can be used for gas separation.

Citation Information

Patent Citations

  • Porous zinc-based MOF material with high thermal stability, and preparation method and application thereof

    CN113174054A

  • Dye / metal-organic framework composite material for anti-counterfeiting and information encryption and preparation method thereof

    CN114479825A

  • Zinc-based metal organic framework material Zn-DPT-PTOBA as well as preparation method and application thereof

    CN115894960A

  • Zinc-based metal organic framework material, preparation method thereof and application of zinc-based metal organic framework material in ethylene separation

    CN116082657A

  • Zn-MOF material for acetylene and ethylene mixed gas separation as well as preparation method and application of Zn-MOF material

    CN117487187A